Tanshinone I Inhibits Oxidative Stress–Induced Cardiomyocyte Injury by Modulating Nrf2 Signaling - Wu, Yu-Ting; Xie, Ling-Peng; Hua, Yue; Xu, Hong-Lin; Chen, Guang-Hong; Han, Xin; Tan, Zhang-Bin; Fan, Hui-Jie; Chen, Hong-Mei; Li, Jun; Liu, Bin; Zhou, Ying-Chun (Frontiers in Pharmacology, 2021)
Cardiovascular disease (CVD), a disease caused by many pathogenic factors, is one of the most common causes of death worldwide, and oxidative stress plays a major role in its pathophysiology. Tanshinone I (Tan I), a natural compound with cardiovascular protective effects, is one of the main active compounds extracted from Salvia miltiorrhiza. Here, we investigated whether Tan I could attenuate oxidative stress and oxidative stress-induced cardiomyocyte apoptosis through Nrf2/MAPK signaling in vivo and in vitro. We found that Tan I treatment protected cardiomyocytes against oxidative stress and oxidative stress-induced apoptosis, based on the detection of relevant oxidation indexes such as reactive oxygen species, superoxide dismutase, malondialdehyde, and apoptosis, including cell viability and apoptosis-related protein expression. We further examined the mechanisms underlying these effects, determining that Tan I activated nuclear factor erythroid 2 (NFE2)-related factor 2 (Nrf2) transcription into the nucleus and dose-dependently promoted expression of Nrf2, while inhibiting MAPK signaling activation, including P38MAPK, SAPK/JNK, and ERK1/2. Nrf2 inhibitors in H9C2 cells and Nrf2 knockout mice demonstrated aggravated oxidative stress and oxidative stress-induced cardiomyocyte injury; Tan I treatment suppressed these effects in H9c2 cells; however, its protective effect was inhibited in Nrf2 knockout mice. Additionally, the analysis of surface plasmon resonance demonstrated that Tan I could directly target Nrf2 and act as a potential Nrf2 agonist. Collectively, these data strongly indicate that Tan I might inhibit oxidative stress and oxidative stress-induced cardiomyocyte injury through modulation of Nrf2 signaling, thus supporting the potential therapeutic application of Tan I for oxidative stress-induced CVDs.